Stock Market Development and Cross-Country Differences in Relative Prices - Larrain, Borja (The Review of Economics and Statistics, 2010)
We document a positive correlation between stock market capitalization and price levels (wages) within the group of countries with poorly developed stock markets and a negative correlation between these two variables within the group of countries with more developed stock markets. This paper argues that there is a causal relationship behind these correlations. Stock markets initially stimulate growth, pushing the demand for nontradables and increasing prices and wages. Stock markets also promote a shift toward more capital-intensive technologies in the tradable sector, increasing the migration of workers to services and eventually putting downward pressure on wages and prices.